1995
DOI: 10.1074/jbc.270.7.3074
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Apoptotic Neuronal Death by GM1 Ganglioside

Abstract: We have used serum-deprived cultures of wild type and genetically modified PC12 cells to investigate the molecular mechanisms by which monosialoganglioside (GM1) rescues neuronal cells from apoptotic death elicited by withdrawal of trophic support. Our findings indicate that GM1-promoted survival can be mediated in part by the Trk NGF receptor as well as by TrkB, and potentially by tyrosine kinase receptors for additional neurotrophic growth factors. Experiments employing K-252a, an inhibitor of Trk kinases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
139
0
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 68 publications
2
139
0
4
Order By: Relevance
“…In cultured cerebellar granule cells, a natural ganglioside, GM1 (6), as well as other synthetic gangliosides, block glutamate-mediated cell death without affecting the function of NMDA or other glutamate-operated cation channels (37). Interestingly, GM1, which does not affect synthesis of neurotrophins, has been shown to mimic neurotrophin activity by increasing Trk function (28,38,39). When compared with BDNF, both GM1 and NMDA elicit a modest increase in Trk tyrosine phosphorylation; however, both compounds prevent glutamate excitotoxicity, suggesting that there could be cross-talk between two or more signaling pathways resulting in a synergism or potentiation of the effect, perhaps via different substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cerebellar granule cells, a natural ganglioside, GM1 (6), as well as other synthetic gangliosides, block glutamate-mediated cell death without affecting the function of NMDA or other glutamate-operated cation channels (37). Interestingly, GM1, which does not affect synthesis of neurotrophins, has been shown to mimic neurotrophin activity by increasing Trk function (28,38,39). When compared with BDNF, both GM1 and NMDA elicit a modest increase in Trk tyrosine phosphorylation; however, both compounds prevent glutamate excitotoxicity, suggesting that there could be cross-talk between two or more signaling pathways resulting in a synergism or potentiation of the effect, perhaps via different substrates.…”
Section: Discussionmentioning
confidence: 99%
“…They have been implicated in several biological processes including cell-cell recognition, regulation of cell growth and differentiation and signal transduction [20]. The ganglioside GM-1 has previously been shown to act as a survival factor in both neuronal cells and cardiac fibroblasts [21,22]. Maulik et al [23] initially showed that GM-1 can reduce I/R injury in an isolated rat heart by Langendorff technique and had suggested that the likely mechanisms included inhibition of calcium overloading and scavenging of free radicals generated during the reperfusion of myocardium.…”
Section: Sphingolipids and Myocardial I/r Injurymentioning
confidence: 99%
“…Thus, apoptosis can be mimicked by the addition of exogenous, soluble C 2 -or C 6 -ceramides or bacterial sphingomyelinase and sphingosine derivatives, but cannot be induced by other lipids (apart from sphingosine whose role in apoptosis is also under investigation) or by other lipases (such as phospholipase C). In fact, both diacylglycerol (35) and gangliosides, specifically, G M1 (36,37), have been reported to have a protective effect indicating that the exogenous ceramide did not induce apoptosis by a nonspecific membrane effect. However, whether ceramide is necessary for any and/or all types of apoptosis and the time course of its action remains to be fully elucidated.…”
mentioning
confidence: 99%